Gastroenterology services for patients with Cystic Fibrosis across Australia and New Zealand: a multi-stakeholder assessment of patients' and professionals’ perspectives - Katz, Tamarah E.; Wakefield, Claire E.; Signorelli, Christina; Day, Andrew S.; Vernon-Roberts, Angharad; Ooi, Chee Y. (Frontiers in Pediatrics, 2023)
International research has highlighted that GI care for this group of patients is lacking.Gastroenterology services to CF clinics across Australasia are yet to be examined. This study aimed to describe the current service delivery model and identify areas for improvement that may lead to positive patient outcomes.CF clinicians (dietitians, clinical nurse consultants, respiratory consultants), gastroenterologists (GE), and patients or their carers from Australia and New Zealand (NZ) were surveyed online to gather their opinions on CF gastroenterology services provided in their region. Data were analysed using descriptive statistics (frequencies and percentages).Likert scale questions were analysed by grouping responses 1-5 and 6-10, presented alongside the median and interquartile range (IQR). Mann-Whitney U and chi-square tests were used to look at differences between stakeholder groups.One hundred and fifty-six health professionals and 172 patients or their carers completed the survey. Results showed that the current GI model of care is predominantly a publicly funded service delivered outside of CF clinic time. GE are largely not integrated into the CF team and report a lack of training opportunities. There is a higher level of dissatisfaction with the current service model in NZ than Australia.No stakeholder group deemed the current CF gastroenterology service model as adequate, leaving opportunity for transformations in this field. Ideally this study will invigorate the need for promotion and integration of GI services that would ultimately benefit the whole CF community.